First report of Cytauxzoon sp. infection in a domestic cat from Portugal. Issue 1 (December 2016) - Alho, Ana; Silva, Joana; Fonseca, Maria; Santos, Filipa; Nunes, Cláudia; de Carvalho, Luís; Rodrigues, Manuel; Cardoso, Luís
Abstract Background Cytauxzoonosis is an emerging and life-threatening tick-borne feline disease caused by haemoprotozoan parasites of the genusCytauxzoon . Information regarding epidemiological and clinical presentation of infections by species other thanCytauxzoon felis is scant. A case ofCytauxzoon sp. infection is described in a 2-year-old mixed breed male domestic cat from Portugal, presenting a history of acute lethargy, anorexia and pyrexia. Results Complete blood count revealed a severe anaemia, leucocytosis and thrombocytopenia. A pleural effusion was noticed on thoracic radiograph, and marked splenomegaly and free abdominal fluid were visualized by ultrasound. A molecular screening for the detection of causative agents of infectious anaemia was performed, and a positive result for Piroplasmorida was obtained. DNA sequencing of a 743 bp amplicon of the 18S rRNA gene (GenBank accession no. KU710344) revealed 99.9 % identity withCytauxzoon manul . Conclusions This is the first report ofCytauxzoon sp. (clustering together withC. manul ) in a felid from Portugal. Clinical manifestations along with molecular analysis suggest the hypothesis that domestic cats might be infected with and serve as a reservoir host forC. manul .